The effects of land titling in Tanzania - Jehovaness Aikaeli; Thomas Markussen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We use household survey data to investigate the effects of formal, private property rights to agricultural land on agricultural investment, land valuation and access to credit in Tanzania. Results show that while there are no detectable effects of formal, private land property rights (written documentation of ownership) on agricultural investment, land ownership documents nevertheless increase the market value of land substantially (more than 25 percent). One reason appears to be that well-documented private property rights facilitate the use of land as collateral for loans and therefore eases access to credit. The findings suggest that there are potentially significant, economic returns to systematic land titling in Tanzania and other countries, although more research is needed to firmly establish this conclusion.
Keywords: O12; O13; P26; Q15; 330; property rights; land titling; agriculture; investment; credit; Tanzania